Methyl-3-(2-hydroxy-5-nitrophenyl amino)-3-phenylpropanoate Based Colorimetric Sensor for Oxyanions - Venty Suryanti; Fajar Rakhman Wibowo; Sekar Handayani (Indonesian Journal of Chemistry, 2020)
A colorimetric anion sensor of methyl-3-(2-hydroxy-5-nitrophenyl amino)-3-phenylpropanoate bearing –OH and –NH groups as binding sites and nitrophenyl as a signaling unit, has been successfully accomplished. The compound functioned as a colorimetric chemosensor for H2PO4– and AcO–, in particular, the sensor showed significant naked-eye detectable color change from colorless to light yellow. In contrast, no color change was detected upon addition of other anions such as SO42–, NO3–, and CIO4–. The anion sensing ability of the sensor was further investigated by UV-Vis absorption spectroscopy in acetone. Characteristic UV-Vis spectra changes were revealed upon addition of H2PO4– and AcO–.